Um estudo do comportamento dos zeros dos Polinômios de Gegenbauer - Afonso, Rafaela Ferreira (2016)
In this dissertation, we study the Sturm Liouvile's theorems for the zeros of the solutions of linear differential equations of second order. These classical theorems are applied to analysis of the monotonicity of functions involving the zeros of classical orthogonal polynomials. in particular, Gegenbauer polynomials.